2020
DOI: 10.29328/journal.japch.1001016
|View full text |Cite
|
Sign up to set email alerts
|

Child neglect - still a neglected problem in the global world: A review

Abstract: Child neglect is a global problem that involves large costs for both the individual and for society. This article is based on published reviews and meta-analyses in the field of child neglect between 1980 and 2018. Of a total of 433 articles, 13 was included, main Data bases has been PubMed, Scopus, Web of Science, Psych Info, ERIC, CINAHL. The prevalence in the normal population was found to be between 16 and 26 percent, while the prevalence in clinical groups seem to be significantly higher. For example, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
4
0
1
Order By: Relevance
“…The findings of this systematic review indicated that victims of child sexual abuse experienced psychological consequences such as feeling lonely, attempt to commit suicide, fear of males, and verbal and physical aggressiveness. This finding is supported by previous systematic reviews [ 24 , 55 , 61 64 ]. Similarly, unwanted pregnancies, underwent an abortion, pain during urination, and vaginal discharge were sexual and reproductive health consequences reported by victims of child sexual abuse, which is supported by previous findings [ 24 , 61 , 63 , 65 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings of this systematic review indicated that victims of child sexual abuse experienced psychological consequences such as feeling lonely, attempt to commit suicide, fear of males, and verbal and physical aggressiveness. This finding is supported by previous systematic reviews [ 24 , 55 , 61 64 ]. Similarly, unwanted pregnancies, underwent an abortion, pain during urination, and vaginal discharge were sexual and reproductive health consequences reported by victims of child sexual abuse, which is supported by previous findings [ 24 , 61 , 63 , 65 ].…”
Section: Discussionsupporting
confidence: 90%
“…This could be because of children living with disability are more vulnerable to emotional, sexual, and physical abuse and neglect than non-disabled children [ 53 , 54 ]. Similarly, children who lack open discussion on sexual issues with parents were more likely to experience sexual abuse, which is supported by a previous systematic reviews [ 55 ]. This could be due to less parental involvement in children’s sexual and reproductive health behaviors which leads to missing opportunities to acquire experiences and life skills for the prevention of sexual abuse.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…An alternative explanation would be spontaneous maturation, which in that case could have happened without the special interventions of the TBF-model, or without foster care. However, previous studies of the effects of foster care or of maltreated children who have not been placed in foster care do not show that such spontaneous maturation usually happens (Engler et al, 2020;Goemans et al, 2015;Goemans et al, 2016;Gypen et al, 2017;Nilsson & Tingberg, 2020;Pecora et al, 2009).…”
Section: Discussion Of Findingsmentioning
confidence: 97%
“…In relation to a child's welfare, neglect can be described as the state of a child being uncared for or the situation in which a child is not being properly taken care of. Tingberg and Nilsson see child neglect as the absence of things, an omission of care needed by a child [2].…”
Section: Literature Review 21 Meaning Of a Child Neglect And Child Ne...mentioning
confidence: 99%